1446. The Impact of Enterobacteriaceae Isolate Breakpoints on Prescriber Treatment Choices for Discordant Pattern Urinary Tract Infections - Lee, Philip (Open Forum Infect Dis, 2019)
BACKGROUND: Our institution revealed Enterobacteriaceae with discordant cefazolin (CEF)-resistant / ampicillin-sulbactam (SAM) susceptible patterns (CRASS-P). This discordance could be from the multiple MIC cephalosporin breakpoint adjustments from CLSI. SAM has higher resistance for gram-negative bacteria compared with cephalosporins such as CEF which is confirmed by our antibiogram. We sought to understand if narrow-spectrum antibiotic choices for CRASS-P urinary tract infections (UTIs) led to clinical cure (CC). METHODS: We conducted a retrospective review from January 2018 to February 2019 of all CRASS-P Escherichia coli, Proteus mirabilis, and Klebsiella pneumoniae isolates from urine cultures. Patients with any symptom related to a UTI, urinalysis with >10 white blood cells/high-powered field, urine culture with >10,000 colony-forming units/mL, and receipt of an antibiotic were included. CC was defined as symptom resolution within 48 hours with no return to care within 28 days of the positive urinary culture. “Group A” included patients prescribed narrow-spectrum antibiotics such SAM, CEF, or an oral cephalosporin (OC) vs. broad-spectrum antibiotics such as ceftriaxone, quinolones or sulfa-medications (“Group B”). RESULTS: There were 960/1356 (70.8%) CRASS-P urinary isolates and 244 patients met inclusion criteria. Of 244 patients, 72 were in Group A and 172 were in Group B. There was no difference in the diversity of the 3 uropathogens, P = 0.34 (Table 1). Median age was 69±20.3 and 67.5±23.9 years for Group A and Group B, respectively, P = 0.23. Females accounted for 73.6% and 77.9% in Group A and B, respectively, P = 0.51. Overall, patients reached CC in 98.6% (71/72) of Group A patients, compared with 92.4% (159/172) of Group B patients, P = 0.07. Antibiotics used in treatment are outlined in Figure 1. UTI was associated with bacteremia for 2 patients in Group A and 4 patients in Group B (P = 0.84). Both patients in Group A reached CC and used AMC for treatment. However, 1 out of 4 patients did not achieve CC in Group B. CONCLUSION: The use of SAM or OC can spare the broad-spectrum antibiotics use for CRASS-P UTIs as there was no statistical difference in CC between the two groups. The use of SAM with CRASS-P bacteremia secondary to UTI is possible; however, future studies are needed. [Image: see text] [Image: see text] DISCLOSURES: All authors: No reported disclosures.